Application of modular holders in welding operations - Barylski, Adam (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2019)
The paper presents examples of the use of folding handles in several selected welding operations. Object designed equipment are being studied in the welding of three body or lever type blanks. The configuration of this type of modular holders uses elements produced in series by Bernd Siegmund GmbH. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)